"Behind the Façade: Motivations for Cosmetic Usage by Women". (December 2021) - Robertson, Julia M.; Kingsley, Barbara E.
Given the wealth of literature on appearance manipulation generally, it is, perhaps, surprising that cosmetic usage receives so little empirical attention, and perhaps reflects a patriarchal approach to "appropriate" research areas. Incorporating a postfeminist approach, the current study aims to address, in part, this lacuna by providing a contemporary synopsis of the various and diverse motivations for cosmetic usage. Online, written responses to a semi-structured questionnaire were collected. In response to six broad questions, for example, "Why do you currently use cosmetics?", respondents were encouraged to write, in as much detail as they liked, on their motivations for using cosmetics. Thematic analysis, using deductive and inductive approaches, revealed four main themes: "Multiple selves"—Conformity, Impression Management, and Judgment; Enhancement and Confidence; Fun, Creativity and Well-being; and Signification and Identity. Whilst some of these themes had been anticipated and, indeed, sign-posted in prior literature, the weight of interest in particular areas was unexpected (e.g., in terms of Fun, Creativity, and Well-being), whilst other areas did not receive the expected attention (e.g., in mate attraction). Additionally, and worthy of future research, entirely new areas also emerged (e.g., cosmetics for fun and creativity).